Determinação eletroanalítica de corante reativo presente como contaminante em proteínas purificadas por cromatografia de afinidade - Osugi, Marly E. [UNESP]; Guaratini, Claudia C. I. [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Sociedade Brasileira de Química, 2004)
Procion Green HE-4BD is a reactive dye currently used in affinity purification, and commonly present as a contaminant in the final biological preparation. An assay method is described to determine trace amounts of the dye in the presence of human serum albumin(HSA) and leakage from agarose as affinity sorbent by cathodic stripping voltammetry. The proposed method is based on the reductive peak at -0.55V in B-R buffer pH 3 (E=0V and t= 240s), obtained when samples of HSA 2% (m/v) containing dye concentrations in sodium hydroxide pH 12 are submitted to a heating time of 330 min at 80 ºC. Linear calibration curves can be obtained for RG19 dye concentrations from 5x10-9 mol L-1 to 8 x10-8 mol L-1. The detection limit (3sigma) is 1x10-9 mol L-1.
Electroanalytical determination of a reactive dye currently used in affinity chromatography for protein purificaton
Keywords: triazine dyes; cathodic stripping voltammetry; purified biomaterials